JLIV 2020
DOI: 10.46534/jliv.2020.07.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Green Roof Research in North America: A Recent History and Future Strategies

Abstract: Since the year 2000, green roof and living architecture research has progressed significantly in North America. For future growth in the implementation of living architecture, there is still a great need for additional and expanded research on green roofs and as yet undefined innovative J. of Living Arch 7(1) Feature 28 green infrastructure. This paper provides an overview of priority topics that have been critical to past success in green roofs, and those that are promising but need future investment, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 120 publications
(181 reference statements)
1
4
0
Order By: Relevance
“…An argument could be made here to choose sedum species with fewer red shades and/or attempt to influence the way which the roofs undergo succession, which could improve how the public experience green roofs. This approach would be in line with the ambition to create and improve harmony between physical environment, human experiences and ecosystems (Bhadouria et al, 2023). The results from this study build on recent studies (Yilmaz et al, 2018;Thorpert et al, 2023), showing that from a cultural ecosystem perspective, landscape professionals have an opportunity to influence the visual expression of green installations through conscious planning and design and thereby influence the viewer´s aesthetic satisfaction.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…An argument could be made here to choose sedum species with fewer red shades and/or attempt to influence the way which the roofs undergo succession, which could improve how the public experience green roofs. This approach would be in line with the ambition to create and improve harmony between physical environment, human experiences and ecosystems (Bhadouria et al, 2023). The results from this study build on recent studies (Yilmaz et al, 2018;Thorpert et al, 2023), showing that from a cultural ecosystem perspective, landscape professionals have an opportunity to influence the visual expression of green installations through conscious planning and design and thereby influence the viewer´s aesthetic satisfaction.…”
Section: Discussionsupporting
confidence: 70%
“…The options for establishing new ground vegetation in cities are often space-limited, so green roofs and green walls provide an important approach for enhancing urban vegetation. While the contribution to various ecosystem services from green roofs and walls is often more limited compared to green spaces and large street trees, they do provide vital ecosystem services that could contribute towards improving quality of life for the urban population (Oberndorfer et al, 2007;Bousselot et al, 2020). This is particularly true for densely built areas where space is limited for other types of vegetation, and green roofs and walls provide the only means for regreening.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is essential that methods between research institutions are aligned so that results can be more easily compared [65]. More long-term ecosystem studies can ensure better understanding of the variation in the integrated biological solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite studies showing that fungi can impact green roof health and function (Fulthorpe et al, 2018;John et al, 2014John et al, , 2017Marttinen et al, 2020;Young et al, 2015), there is a lack of research on drivers of microbial diversity on green roofs (Fulthorpe et al, 2018). In fact, Bousselot et al (2020) recently identified microbial populations in the substrate and their responses in the green roof system as a key gap in green roof research in need of addressing. Green roofs are an example of a relatively novel ecosystem (Hobbs et al, 2006), characterized by low diversity and heavily managed plant communities grown in engineered substrate (Dunnett & Kingsbury, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite studies showing that fungi can impact green roof health and function (Fulthorpe et al, 2018 ; John et al, 2014 , 2017 ; Marttinen et al, 2020 ; Young et al, 2015 ), there is a lack of research on drivers of microbial diversity on green roofs (Fulthorpe et al, 2018 ). In fact, Bousselot et al ( 2020 ) recently identified microbial populations in the substrate and their responses in the green roof system as a key gap in green roof research in need of addressing.…”
Section: Introductionmentioning
confidence: 99%